Blowing in the Wind : Using a Consumer Drone for the Collection of Humpback Whale (Megaptera novaeangliae) Blow Samples during the Arctic Polar Nights - Gomes Costa, Helena Sofia; Rogan, Andrew; Zadra, Christopher; Larsen, Oddbjørn; Rikardsen, Audun H.; Waugh, Courtney Alice (Drones, 2023)
publishedVersion